EVALUASI KEBIJAKAN SISTEM PROTEKSI KEBAKARAN PADA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA PEKANBARU TAHUN 2019 - Saputri, Asesta; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Fire protection system is a system consisting of completeness equipment and facilities, both installed and built in buildings that are used for active, passive protection systems and management methods in order to protect buildings and the environment against fire hazards (Regulation of the Minister of Public Works Number 26 / PRT/ M/ 2008). Fire protection systems can be grouped into two parts, namely active and passive. An active fire protection system is a complete fire protection system consisting of manual and automatic fire detection systems, water-based fire extinguishing systems such as sprinklers, standpipes and fire hoses, as well as chemical-based fire extinguishing systems such as small fire extinguishers and special extinguishers (Regulation). Minister of Public Works Number 26/PRT/M/2008 Meanwhile, a passive protection system is a means, system or design that is part of the system so that it does not need to be actively driven. This research was conducted at the Pekanbaru City Fire and Rescue Service. The purpose of this study is to describe and analyze the Evaluation of the Fire Protection System Policy at the Pekanbaru City Fire and Rescue Service. The theory used is the theory of Dunn, 1998: 405 in Subarsono Ag, 2006:126. The research method used is descriptive qualitative with interview and documentation data collection techniques, the type of data used is secondary data and primary data. The results of this study are that every building is required to have a fire protection device that is useful to ensure the safety and comfort of building occupants.Â Keywords: Policy Evaluation, Fire Protection System.